X-Men [videorecording (Blu-Ray)] - Singer, Bryan, 1965-; Jackman, Hugh; Stewart, Patrick, 1940-; McKellen, Ian; Janssen, Famke, 1964-; Berry, Halle; Marsden, James, 1973-; Davison, Bruce, 1946-; Romijn, Rebecca, 1972-; Paquin, Anna (20th Century Fox Home Entertainment, 2009)
Outcasts since birth, the X-Men are the next step of human evolution. Born with unique genetic mutations that give them extraordinary powers, they battle on the side of good. Now they must use their powers to save the people that fear them.